Continuous Renal Replacement Therapy for Two Neonates With Hyperammonemia - Markham, Christopher; Williams, Caroline; Miller, Cory; Grange, Dorothy K.; Davis, T. Keefe; Remy, Kenneth E. (Frontiers in Pediatrics, 2021)
Objectives: This study aims to assess the feasibility of using hemofiltration for ammonia clearance in low body weight infants with an inborn error of metabolism. Design: A study of two cases Setting: Quaternary pediatric hospital neonatal and pediatric intensive care unit Patients: Infants less than six months of age with an ICD-9 diagnosis of 270.6 (hyperammonemia) Interventions: Continuous renal replacement therapy (CRRT) Measurements and main results: We measure serum ammonia levels over time and the rate of ammonia clearance over time. CRRT was more effective than scavenger therapy alone (AmmonulTM) for rapid removal of ammonia in low weight infants (as low as 2.5kg). Conclusions: CRRT is technically feasible in low weight infants with severe hyperammonemia secondary to an inborn error of metabolism.